ACTFL معيار جودة تعليم اللغة العربية في المدرسة الثانوية في أندونيسيا على أسس معيار - Fathi Hidayah Hidayah (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2019)
Quality is a business oriented to customer or user satisfaction. In the world of learning, quality is closely related to the outcome achieved after the learning process. Similarly with Arabic Learning. In Indonesia, Arabic is taught from the level of Madrasah Ibtidaiyyah to Higher Education especially those under the auspices of the Ministry of Religious Affairs. As a non-Arabic speaking country, Indonesia has a high learning Arabic interest. This expectation is then used as a standard in the acquisition of learning Arabic. Therefore, the curriculum, as a standard of learning process must be adjusted to foreign language learning standards, one of which is made by ACTFL. The ACTFL (American Councils on the Teaching of Foreign Language) is a national association for professional language education from all levels of teaching and represents all languages including Arabic. In detail, ACTFL provides an explanation of Arabic skills and samples that are intended to assist Arabic teachers, students and assessment specialists according to predetermined standards that include four skills in Arabic (istima ', kalam, qira'ah, and kitabah ).This study aims to obtain an analysis of standard Arabic language learning in madrasah in Indonesia based on ACTFL standards. Content analysis in the form of Madrasah Tsanawiyah curriculum document and ACTFL 2012 Proficiency Guidance document. The results of this study indicate that the standard of learning Arabic in Islamic schools in Indonesia is at the level of novice law hing novice mid for the fourth maharah. This indicates that the standard of learning Arabic in Indonesia is in accordance with the standards applicable at the international level, so that basically been able to meet the expectations of its users. Keywords: Quality, Arabic Curriculum at Madrasa Tsanawiya, ACTFL Standards